Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/jp506113g
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling How an Archetypal Fluorescent Protein Operates: Theoretical Perspective on the Ultrafast Excited State Dynamics of GFP Variant S65T/H148D

Abstract: Green fluorescent protein variant S65T/H148D has been reported to host a photocycle involving the photoinduced proton transfer reaction between the chromophore and residue Asp148 under 50 fs and without a measurable kinetic isotope effect, and experimental evidence is suggestive of the existence of a highly delocalized proton between these residues. The blinding speed at which this biological system undergoes proton transfer has been ascribed to the extreme increase of acidity of the GFP chromophore in the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 62 publications
4
42
0
Order By: Relevance
“…38,39 In order to obtain a relatively long time of QM/MM simulation, we used an approach previously used by us with notable success. 21 In short, this approach requires the computation of a precursor trajectory from which to sample the starting configurations for several independent trajectories on which averaging is to be performed. The protocol followed was the same as that in our previous study, allowing us to simulate 1.0 ns at 300 K. In the case of E222Q/H148D a previous extra QM/MM equilibration of 40 ps was performed to ensure that the mutations manually introduced were accommodated.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…38,39 In order to obtain a relatively long time of QM/MM simulation, we used an approach previously used by us with notable success. 21 In short, this approach requires the computation of a precursor trajectory from which to sample the starting configurations for several independent trajectories on which averaging is to be performed. The protocol followed was the same as that in our previous study, allowing us to simulate 1.0 ns at 300 K. In the case of E222Q/H148D a previous extra QM/MM equilibration of 40 ps was performed to ensure that the mutations manually introduced were accommodated.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Particularly informative were mutations in the vicinity of the proton wire (Figure 1). Both the S65T mutation and replacement of E222 disrupt the proton transfer chain, so no I* emission occurs on excitation of A; however, a further mutation (H148D) rewires proton transfer, via a short low‐barrier H‐bond to D148, to which ESPT occurs on a sub‐picosecond time scale 2a. 7 In contrast, mutations T203V and T203Y shift the emission of I*, but do not significantly alter ESPT.…”
Section: Relaxation Times Associated With the States Shown In Figure mentioning
confidence: 99%
“…All PE profiles were close to isoergic. However, no evidence could be found for the postulated extreme drop in pK a * value of Tyr66, 26 which had originally been derived from a theoretical study of the chromophore in solution and in a conformation in which both rings were co-planar. The situation was found to be different in the protein: accounting for the effects of the protein surroundings led to an estimate of the pK a * decrease that was much smaller.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] In this spirit, some of us performed a detailed study of the ground state of GFP S65T/H148D with the goal of explaining the reasons behind this ultrafast process. 25,26 Using quantum mechanical/ molecular mechanical (QM/MM) and molecular dynamics (MD) methods the geometry of the Cro-Asp148 unit was satisfactorily reproduced. 25 Moreover, QM potential energy (PE) profiles for proton transfer in the ground and excited electronic state of several snapshots from these simulations revealed that the proton transfer becomes more favored upon photoexcitation.…”
Section: Introductionmentioning
confidence: 99%